Increased Expression of PPAR-γ Modulates Monocytes Into a M2-Like Phenotype in SLE Patients: An Implicative Protective Mechanism and Potential Therapeutic Strategy of Systemic Lupus Erythematosus - Liu, Yu; Luo, Shuangyan; Zhan, Yi; Wang, Jiayu; Zhao, Rui; Li, Yingjie; Zeng, Jinrong; Lu, Qianjin (Frontiers in Immunology, 2021)
Systemic lupus erythematosus (SLE) is a spectrum of autoimmune disorders characterized by continuous inflammation and the production of autoantibodies. Monocytes, as precursors of dendritic cells and macrophages, are involved in the pathogenesis of SLE, particularly in the inflammatory reactions. Previous studies have proved that Pam3CSK4, as a synthetic ligand of TLR2, could stimulate monocytes to differentiated into a M2-like phenotype which presented immunosuppressive functions. However, the underlying mechanisms remain to be further studied. Here, we reported an increased expression of PPAR-γ in the CD14+ monocytes from SLE patients, particularly in the treated group of SLE patients and the group with positive anti-dsDNA antibodies. Additionally, PPAR-γ expression decreased in the SLE patients with skin lesion. Furthermore, we demonstrated that Pam3CSK4 stimulation can decrease the expression of CCR7, CD80, IL-1β, IL-6, IL-12, and NF-κB which were related to the M1-like subset of monocytes and increased the expression of ARG1 which was related to the M2-like subset through upregulated PPAR-γ expression and consequently downregulated NF-κB expression in the CD14+ monocytes in a time-dependent manner. ChIP-qPCR results further demonstrated that Pam3CSK4 pretreatment could modulate PPAR-γ expression by regulating histone modification through the inhibition of Sirt1 binding to the PPAR-γ promoter. Taken together, our study indicated a protective role of TLR2/Sirt1/PPAR-γ pathway in the pathogenesis of SLE which provided potential therapeutic strategies.